Pendampingan Optimalisasi Penggunaan Aset untuk Kesejahteraan Masyarakat Desa di Wilayah Kecamatan Sungai Raya - Sumarno, Dwi Agus; Nurhadi, Nurhadi; Seran, Silverius Tey (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2024)
The purpose of this community service activity is to enhance the knowledge and experience of village governments in Sungai Raya District, Kubu Raya Regency, so that they can better utilize the village's potential through village asset management to improve the welfare of the villagers. In the future, the results of optimizing these village assets can be taken into consideration in the development of rural areas in Sungai Raya District by utilizing village assets such as natural resources and other physical assets and generating income for the community. The activities conducted include Forum Group Discussion (FGD), training, and mentoring aimed at optimizing village assets and enhancing the institutional capacity of village groups and communities, namely: Village Officials, Village-Owned Enterprises (Bumdesa), and the local community. The participants involved in this activity are planned to be 20 people who are village officials in Sungai Raya District, Kubu Raya Regency. The methods used in this activity include lectures and Q&A sessions on village asset management regulations, providing technical training on filling out village asset recording applications in the form of empowerment, and mentoring in village assets control. Specifically, this community service activity has achieved several objectives, including the establishment of commitment among village officials in optimizing village asset management in each village in Sungai Raya District, including (1) optimizing available natural resources, (2) agricultural potential, and (3) technology utilization. Villages in Sungai Raya District have not optimized the management of village assets or wealth for the sustainability of the village assets they possess.